The Development of the Halal Industry in Indonesia: An Analysis of Innovation and Export Potential - Rizkitama, Gebie Yoga Efrizal; Fatwa, Nur; Muttaqin, Mohammad Izdiyan (Enrichment: Journal of Multidisciplinary Research and Development, 2025)
This systematic literature review examines the development of Indonesia's halal industry, focusing on the role of innovation and its contribution to export potential. Through a comprehensive analysis of 17 recent studies (2019-2024), the research investigates key innovations driving industry development and their impact on enhancing Indonesia's position in the global halal market. The review identifies several significant innovations, including digital traceability systems, the Penta Helix collaboration model, specialized halal industrial zones, and simplified certification processes. These innovations have demonstrated substantial contributions to export growth through improved product quality, enhanced market access, and strengthened competitive advantages. The findings reveal that successful export expansion requires a comprehensive approach to innovation encompassing technological advancements, process improvements, and strategic market development. The study highlights the importance of stakeholder collaboration, regulatory framework development, and sustainability integration in driving industry growth. While challenges remain, particularly in standardization and regulatory compliance, the research suggests that continued innovation across all aspects of the halal industry is crucial for maintaining and expanding Indonesia's export potential in the increasingly competitive global halal market. The review contributes to the understanding of how innovation drives halal industry development and provides practical implications for stakeholders seeking to enhance Indonesia's position in the global halal trade.